Profiles of criminal justice system involvement of mentally ill homeless adults. (March 2016) - Roy, Laurence; Crocker, Anne G.; Nicholls, Tonia L.; Latimer, Eric; Gozdzik, Agnes; O'Campo, Patricia; Rae, Jennifer
Abstract: Objectives: This study aims to examine the rates of self-reported contacts with the criminal justice system among homeless adults with mental illness, to identify the characteristics of participants who have had contacts with the criminal justice system, to report the dimensional structure of criminal justice system involvement in this sample, and to identify typologies of justice-involved participants. Methods: Self-report data on criminal justice system involvement of 2221 adults participating in a Canadian Housing First trial were analyzed using multiple correspondence and cluster analysis. Results: Almost half of the participants had at least one contact with the criminal justice system in the 6 months prior to study enrollment. Factors associated with justice involvement included age, gender, ethnic background, diagnosis, substance misuse, impulse control, compliance, victimization, service use, and duration of homelessness. A typology of criminal justice involvement was developed. Seven criminal justice system involvement profiles emerged; substance use and impulse control distinguished the clusters, whereas demographic and contextual variables did not. Conclusions: The large number of profiles indicates the need for a diverse and flexible range of interventions that could be integrated within or in addition to current support of housing services, including integrated substance use and mental health interventions, risk management strategies, and trauma-oriented services.